Eliminating child marriage in Ethiopia: Emerging regularities and practical norms - Fana Gebresenbet Erda (Danish Institute for International Studies (DIIS), 2021)
How can we explain the large gap between national legal and policy commitments to reduce and eliminate gender-based violence (GBV) and the reality and practice of GBV in Ethiopia? Hitherto explanations mainly centre on the conflict between and social and official norms, and the stubbornness of the former. In this new DIIS Working Paper, Fana Gebresenbet tries to go beyond this dichotomy to examine what happens in the 'in-between spaces'. While the stubbornness of social norms only brings home to us the slow pace of change, it does not tell us what guides the emerging practices that contribute towards change. Instead, 'practical norms' are used here as an analytical tool to examine what happens as we move along the continuum from social to official norms. This helps us capture why routinised, coordinated and socially acceptable new practices occur before the major social norms change.
Keywords: 330; Kinder; Ehe; Gewalt; Kinderschutz; Äthiopien